Retinol-binding protein: the transport protein for vitamin A in human plasma - Kanai, Masamitsu (1968)
Vitamin A circulates in human plasma as retinol bound to a specific transport protein. This protein differs from the known low and high density plasma lipoproteins and has a hydrated density greater than 1.21. In order to study this protein, volunteers were injected intravenously with retinol-15-(14)C. Plasma was collected 1-3 days later, and the purification of retinol-binding protein (RBP) was monitored by assaying for (14)C and also by following the fluorescence of the protein-bound retinol. Purification of RBP was effected by the sequence: Cohn fractionation, chromatography on columns of Sephadex G-200 and diethylaminoethyl (DEAE)-Sephadex, preparative polyacrylamide gel electrophoresis, and finally chromatography on Sephadex G-100. These procedures resulted in a preparation of RBP which was at least 98% pure and which had been purified more than 1500-fold. Purified RBP has α(1) mobility on electrophoresis and has a molecular weight of approximately 21,000-22,000. There appears to be one binding site for retinol per molecule of RBP. Solutions of RBP are fluorescent (characteristic of retinol) and have ultraviolet absorption spectra with peaks at 330 mμ (resulting from the bound retinol) and at 280 mμ. There are no fatty acid or fatty acyl chains present in purified RBP. The usual concentration of RBP in plasma is of the order of 3-4 mg/100 ml. In plasma, RBP apparently circulates as a complex, together with another, larger protein with prealbumin mobility on electrophoresis. The RBP-prealbumin complex remains intact during Cohn fractionation and during chromatography on Sephadex and on DEAE-Sephadex columns. The complex dissociates during gel electrophoresis, permitting the isolation and subsequent purification of each of the components. The complex is again formed by mixing together solutions of the separated RBP and of prealbumin. Retinol transport in plasma thus appears to involve both a lipid-protein (retinol-RBP) interaction and a protein-protein (RBP-prealbumin) interaction.